A Dynamic Model of Predation - Patrick Rey; Yossi Spiegel; Konrad O. Stahl (Center for Economic Studies and ifo Institute (CESifo), 2022)
We study the feasibility and profitability of predation in a parsimonious infinite-horizon, complete information setting where an incumbent may face an entrant, in which case it needs to decide whether to accommodate or predate it. If the entrant exits, a new entrant is born with positive probability. We show that there always exists a Markov perfect equilibrium, which can be of three types: accommodation, predation with no future entry, and predation with hit-and-run entry. We use the model to study alternative antitrust policies, derive the best rules for these policies, and compare their welfare effects.
Keywords: D43; L41; 330; predation; accommodation; entry; legal rules; Markov perfect equilibrium